Physical therapy treatment in children with cerebral palsy after single-event multilevel surgery: a qualitative systematic review. A first step towards a clinical guideline for physical therapy after single-event multilevel surgery. (June 2019) - van Bommel, Esther E.H.; Arts, Marieke M.E.; Jongerius, Peter H.; Ratter, Julia; Rameckers, Eugene A.A.
Background: The aim of this study was to review available evidence for physical therapy treatment (PTT) after single-event multilevel surgery (SEMLS), and to realize a first step towards an accurate and clinical guideline for developing effective PTT for children with cerebral palsy (CP) after SEMLS. Methods: A qualitative systematic review (PubMed, Medline, Embase, CINAHL, and the Cochrane Library) investigating a program of PTT after SEMLS in children aged 4–18 years with CP classified by Gross Motor Function Classification System level I–III. Results: Six articles meeting the inclusion criteria were selected. The selected studies provide only incomplete descriptions of interventions, and show no consensus regarding PTT after SEMLS. Neither do they show any consensus on the outcome measures or measuring instruments. Conclusions: Based on the results of this literature review in combination with our best practice, we propose a preliminary protocol of PTT after SEMLS.